2009
DOI: 10.1111/j.1468-0009.2009.00551.x
|View full text |Cite
|
Sign up to set email alerts
|

A Cross‐Sectional Prevalence Study of Ethnically Targeted and General Audience Outdoor Obesity‐Related Advertising

Abstract: Context: Commercial marketing is a critical but understudied element of the sociocultural environment influencing Americans' food and beverage preferences and purchases. This marketing also likely influences the utilization of goods and services related to physical activity and sedentary behavior. A growing literature documents the targeting of racial/ethnic and income groups in commercial advertisements in magazines, on billboards, and on television that may contribute to sociodemographic disparities in obesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
126
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(137 citation statements)
references
References 71 publications
8
126
0
3
Order By: Relevance
“…Lastly, there may be other factors that explain the relationship between deprivation and eating behaviours. For example, the association between fastfood consumption and socio-economic deprivation may reflect the concentration of fast-food restaurants (33) or marketing promotions for less healthy foods (34) in racially segregated areas. This may be particularly relevant in New Zealand as Māori and Pacific populations are overrepresented on indicators of deprivation (27) .…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, there may be other factors that explain the relationship between deprivation and eating behaviours. For example, the association between fastfood consumption and socio-economic deprivation may reflect the concentration of fast-food restaurants (33) or marketing promotions for less healthy foods (34) in racially segregated areas. This may be particularly relevant in New Zealand as Māori and Pacific populations are overrepresented on indicators of deprivation (27) .…”
Section: Resultsmentioning
confidence: 99%
“…15 Following other researches, two ratios were calculated to allow for comparisons across neighborhood categories: outdoor advertising area in square feet per 100,000 people and outdoor advertising area in square feet per square mile. 10 …”
mentioning
confidence: 99%
“…Following previous research, 10 we defined outdoor advertising as ads found on billboards, bus shelters, bus benches, and posters on storefronts large enough to be seen from the street. Observers received 3 h of training on the study purpose and logistics of data collection, with the majority of the time spent practicing field data collection and verifying practice results.…”
mentioning
confidence: 99%
See 2 more Smart Citations